The Constraints-Led approach: Principles for sports coaching and practice design - Renshaw, I.; Davids, K.; Newcombe, D.; Roberts, W. (Routledge, 2019)
For the last 25 years, a constraints-based framework has helped to inform the way that many sport scientists seek to understand performance, learning design and the development of expertise and talent in sport. The Constraints-Led Approach: Principles for Sports Coaching and Practice Design provides students and practitioners with the theoretical knowledge required to implement constraints-led approaches in their work.